Asia and the Pacific SDG Progress Report 2020 - United Nations (United Nations, 2020)
This report analyses trends as well as data availability for monitoring progress toward the Sustainable Development Goals (SDGs) in Asia and the Pacific and its five subregions. It assesses gaps which must be closed to achieve the goals by 2030. This assessment is designed to ensure the region’s actions remain on target, shortcomings are addressed as they arise, and all interested parties remain engaged. It is an invaluable resource for all stakeholders involved in prioritization, planning, implementation and follow-up of the 2030 Agenda for Sustainable Development in Asia and the Pacific.